Task-Based Versus Task-Supported Language Instruction: An Experimental Study - Li, S.; Ellis, Rod; Zhu, Y. (2016)
This study investigated the effectiveness of task-based and task-supported instruction in the acquisition of the English passive construction—a structure about which learners had limited prior knowledge. A total of 150 Chinese middle school English as a foreign language (EFL) learners were randomly assigned to five groups—one control group who only took the pretest and posttests and four experimental groups who attended a 2-hour treatment session where they performed two dictogloss tasks in groups, each including a reporting phase when the learners took turns to tell the narrative. Among the four experimental groups, one just performed the two oral tasks; a second group received explicit instruction before performing the tasks; a third group received within-task feedback but no explicit instruction; and the fourth group received both explicit instruction and within-task feedback. Treatment effects were gauged via a grammaticality judgment test (GJT) and an elicited imitation test (EIT). On the GJT, the conditions with explicit instruction and/or feedback led to significant gains with explicit instruction plus feedback showing the largest effects. On the EIT, there was no effect for any of the three treatment groups when the data were analyzed for the whole cohort. However, when the learners were subdivided into those with zero and some prior knowledge based on their pretest EIT scores, explicit instruction plus within-task feedback was more effective than the other treatment types for the latter.